The Momentum of the Holy Month of Ramadan in Increasing Social and Spiritual Piety for Muslim Society - Parembai, Murni (Jurnal Inovasi Pendidikan MH Thamrin, 2024)
The momentum of the holy month of Ramadan in increasing social piety and spiritual piety for Muslims, an article written to observe a momentum created in the month of Ramadan. There is a seriousness for Muslims in carrying out and increasing their worship because they believe that the month of Ramadan is different from other months. Its greatness and holiness bring many rewards that are multiplied. Not only the spiritual aspect increases, but also social piety. Relations with the community are established on various occasions. Not only fellow Muslims, but also with other religious communities. Various traditions in welcoming this month are carried out which are known as Tarhib Ramadhan like welcoming a guest. One of them is determining the entry of 1 Ramadhan by monitoring the Hilal. Then continued with the Itsbat Session to find an agreement on the beginning of Ramadhan. A full month of worship will leave a positive impact on the souls of Muslims. There is satisfaction, peace, coolness, worship full of coolness and discipline continues outside the month of Ramadan. So that it leaves a longing in the following months. There is a soul that is obedient, obedient, sincere in worship. Social relations with the community are getting better. Harmony is created in social relations.